Is Employee Technological “Ill-Being” Missing from Corporate Responsibility? The Foucauldian Ethics of Ubiquitous IT Uses in Organizations - Leclercq-Vandelannoitte, Aurélie (Journal of business ethics, 2019)
The ethical issues introduced by excessive uses of ubiquitous information technology (IT) at work have received little attention, from either practitioners or ethics scholars. This article suggests the concept of technological ill-being and explores the ethical issues arising from such ill-being, according to the individual and collective responsibilities associated with their negative effects. This article turns to the philosopher Michel Foucault and proposes a renewed approach of the relationship among IT, ethics, and responsibility, based on the concepts of practical rationality, awareness, and self-engagement. This article reports a case study of an international automotive company actively engaged in both corporate social responsibility (CSR) and ubiquitous IT deployment. Technological ill-being is an expression of the tension between an individual’s social attributes and aspirations when using modern IT and a system of norms, rules, and values imposing constraints on him or her. We identify the reasons for the lack of consideration of technological ill-being in CSR through identification of the inclusion–exclusion principle. The resulting critical, comprehensive approach to corporate responsibilities and IT uses incorporates the ethical implications of the latter, highlights the practical rationality of their relationship, and demands both individual and collective responses, through a call for collective ethical awareness and self-engagement. The findings prompt a Foucauldian ethics of IT use in organizations, which emerges in a mutually constitutive relationship between the self, as a moral subject of own actions, and broader organizational principles, in which CSR appears as a techne (i.e., a practical rationality governed by conscious aims).